2007
DOI: 10.1007/s11270-007-9518-6
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Desorption of Dye Remazol Yellow onto a Mexican Surfactant-modified Clinoptilolite-rich Tuff and a Carbonaceous Material from Pyrolysis of Sewage Sludge

Abstract: The sorption behavior of dye remazol yellow using surfactant modified zeolitic rock and a carbonaceous material obtained by pyrolysis of sewage sludge and treated with HCl (1.0%) solution was determined. The kinetic and sorption isotherms experimental results were best adjusted to the pseudosecond order model and to the Langmuir-Freundlich isotherm model which indicate that the sorption process is chemisorption on heterogeneous materials. Remazol yellow could be removed from the saturated modified zeolitic mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 14 publications
2
27
2
2
Order By: Relevance
“…A similar result was found for the adsorption of RY onto the carbonaceous material prepared from sewage sludge (12.72 mg g −1 ) [16], while the adsorption of MG onto the carbonaceous material was superior to that on the commercial activated carbon in the batch system [40].…”
Section: 97)supporting
confidence: 79%
See 3 more Smart Citations
“…A similar result was found for the adsorption of RY onto the carbonaceous material prepared from sewage sludge (12.72 mg g −1 ) [16], while the adsorption of MG onto the carbonaceous material was superior to that on the commercial activated carbon in the batch system [40].…”
Section: 97)supporting
confidence: 79%
“…The removal of RY using carbonaceous material from pyrolyzed sewage sludge treated with 10% HCl was evaluated using adsorption equilibria. The results indicated that the main mechanism involved in the adsorption of the dye was chemisorption on a heterogeneous material [16]. However, MG removal has not been reported for batch adsorption.…”
Section: 97)mentioning
confidence: 92%
See 2 more Smart Citations
“…The Freundlich model has been applied to adsorbents with heterogeneous surfaces and considers multilayer sorption (Torres-Pérez et al 2008), which is given as follows:…”
Section: Freundlich Modelmentioning
confidence: 99%